PERFORMANSI SAPI BALI PADA TIGA DAERAH DI PROVINSI BALI - A. Supriyantono; Luqman Hakim; Suyadi; Ismudiono (The East Java Biological Society, 2008)
The aim of the research was to know qualitative and quantitative traits of Bali cattle at three different areas geographically (lowland, midland and highland) at Bali province whether there are deviations or not. Variation in coat colour and some description about phenotypic Bali cattle are the main aspect for qualitative trait whereas body weight, some statistical vital (height at hip, body lenght, heart girth) and reproduction traits (mating system, origin of sire, condition of physiology, service per conception, calving interval and days open) of Bali cattle are the main aspect for quantitative trait. Sample of Bali cattle was taken in Tabanan (midland), Pulukan (lowland) and Karang Asem (highland) area about 2% of the total population. Each trait was measured at different age group. The age for each cattle was based on permanent incicy (PI) wich divided into 5 PI (PI0, PI1, PI2, PI3, PI4). The qualitative traits were found by direct observation at the field together with measurement of quantitative traits, body weight and some statistical vital. The result showed that in general Bali cattle are sexually dimorphic spesies, with bull being dark chestnut brown and cow and juveniles reddish brown. Both sexes have white rump patches and leggings. Both sexes carry horns, although they are much heavier and larger in the males.Quantitatively, bali cattle in Pulukan are much smaller than any other area followed in lack reproduction traits.